2021
DOI: 10.1007/s00431-021-04221-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal SARS-CoV-2 infection during pregnancy: possible impact on the infant

Abstract: The risk and potential consequences of mother-to-child transmission of severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2) during pregnancy are still a matter of debate. We studied the impact of SARS-CoV-2 infection on 56 complete households, including 27 newborns whose mothers were pregnant when exposed to the virus. Two PCR-confirmed perinatal SARS-CoV-2 transmissions with mild symptoms in affected neonates were recorded. In addition, we observed a severe eye malformation (unilateral microphtha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
1
18
0
4
Order By: Relevance
“…Studies so far have suggested that transmission of SARS-CoV-2 across the placenta is rare 30 , 31 , which likely explains the lack of association. There has, however, been a case report of a severe eye anomaly linked to maternal SARS-CoV-2 infection at 5-6 weeks gestation 32 . We did not identify any eye anomalies in babies exposed to infection in early pregnancy (or their controls), but this highlights the importance of continued monitoring of congenital anomalies following SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies so far have suggested that transmission of SARS-CoV-2 across the placenta is rare 30 , 31 , which likely explains the lack of association. There has, however, been a case report of a severe eye anomaly linked to maternal SARS-CoV-2 infection at 5-6 weeks gestation 32 . We did not identify any eye anomalies in babies exposed to infection in early pregnancy (or their controls), but this highlights the importance of continued monitoring of congenital anomalies following SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…In immune system suppression, there is an increased risk of severe complications, uncertainties in antenatal care, and increased concern about vertical transmission to the fetus ( Lindheimer and Cunningham, 2014 ; Morhart et al, 2021 ). Pregnant women may be one of the groups particularly vulnerable to infections.…”
Section: Introductionmentioning
confidence: 99%
“…[15] However, a case report study suggested that maternal SARS-CoV-2 infection in weeks 5 and 6 of embryonic development was associated with neonatal severe eye malformation. [16] Evidence indicated that in utero transmission of SARS-CoV-2 is possible based on the detection of SARS-CoV-2 in intrauterine tissue samples, such as amniotic fluid, placenta, and umbilical cord plasma. [17] Besides, placental expression of ACE2 and transmembrane protease serine 2 (TMPRSS2) required for SARS-CoV-2 entering the cells makes the transplacental transmission of SARS-CoV-2 theoretically feasible.…”
Section: Maternal and Fetal Outcomesmentioning
confidence: 99%